Pelatihan Produksi Maggot Berbasis Limbah Organik sebagai Upaya Pengelolaan Sampah Berkelanjutan di Kabupaten Takalar - Sahrani U; Sitti Saenab; A.Afrinaramadhani Hatta; Salma Samputri; Putri Damayanti (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Abstract. Organic waste problems that continue to increase require effective and sustainable management solutions. One alternative that can be implemented is the utilization of Black Soldier Fly (BSF) larvae or maggots as bioconversion agents for organic waste. This community service activity aimed to improve community knowledge and skills regarding maggot cultivation based on organic waste as an effort to support sustainable waste management in Takalar Regency. The activity was carried out at PPLH Puntondo involving 19 participants through counseling, interactive discussions, demonstrations, and direct practice of maggot cultivation. The evaluation was conducted using pretests and posttests to measure the improvement of participants’ understanding. The pretest results showed an average score of 53.15, categorized as sufficient, while the posttest results increased to 84.21, categorized as very good. This improvement indicates that participatory training methods are effective in enhancing community knowledge regarding maggot-based organic waste management. In addition, participants gave positive responses to the activity because maggot cultivation was considered easy to apply and provided environmental as well as economic benefits. This activity is expected to encourage active community participation in independent and sustainable organic waste management while also creating opportunities for environmentally. Keywords: BSF maggot, organic waste, waste management, community empowerment